2019
DOI: 10.1177/0011128719890271
|View full text |Cite
|
Sign up to set email alerts
|

Joint Growth Trajectories of Bullying Perpetration and Victimization Among Korean Adolescents: Estimating a Second-Order Growth Mixture Model–Factor-of-Curves With Low Self-Control and Opportunity Correlates

Abstract: Joint growth trajectories of bullying perpetration and victimization were examined using 5-year panel data (2004–2008) from a sample of 2,844 South Korean adolescents between the ages of 11 and 15 (fourth to eighth grade). The second-order growth mixture model revealed three distinct subgroups: bully-victims to low bully-victims transition (9.9%); moderate bully-victims to victim transition (6.8%); and a limited involvement/stable group (83.3%). Respondents with less self-control who associated with delinquent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 77 publications
(127 reference statements)
6
21
0
Order By: Relevance
“…We found a group with both bullying and victimization increased over time (involvement trajectory group, 7.6%). A similar group was found in Barker et al (2008) but not in the other two studies (Cho & Lee, 2019; Haltigan & Vaillancourt, 2014). Why did bullying and victimization increase at almost the same time?…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found a group with both bullying and victimization increased over time (involvement trajectory group, 7.6%). A similar group was found in Barker et al (2008) but not in the other two studies (Cho & Lee, 2019; Haltigan & Vaillancourt, 2014). Why did bullying and victimization increase at almost the same time?…”
Section: Discussionsupporting
confidence: 74%
“…Only a few studies have explored the trajectories of both bullying and victimization in the same sample (Barker et al, 2008; Cho & Lee, 2019; Haltigan & Vaillancourt, 2014). Using a second-order growth mixture model, Cho and Lee (2019) found three distinct subgroups among 2,844 Korean adolescents: a bully-victims to low bully-victims transition group (9.9%), a moderate bully-victims to victims transition group (6.8%), and a limited involvement/stable group (83.3%). Barker et al (2008) conducted research in a sample of British adolescents from early to mid-adolescence.…”
mentioning
confidence: 99%
“…Bullying is defined as intentional and repeated aggression characterized by an imbalance of power between perpetrator (s) and victim (Smith, 2019). Given bullying behavior significantly decreases during late school years (Cho & Lee, 2020), early and middle adolescence are hence target periods for effective intervention to prevent and reduce bullying. In recent years, important insights have arisen from studies on the psychological enablers of face-to-face bullying perpetration.…”
Section: Introductionmentioning
confidence: 99%
“…Parental influence decreases in relative importance after childhood and early adolescence while the influence of peers and school is greater during later adolescence. During middle and later adolescence, South Korean juveniles are more likely to associate with delinquent peers outside their homes and engage in delinquent behavior (Cho et al, 2019; Cho & Lee, 2018, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (2020) found that among four delinquency trajectories (non-delinquents, increasing delinquency, decreasing delinquency, and chronic delinquency) of South Korean adolescents, Agnew's (2005) domains of family, peers, and self signiicantly predicted group trajectory membership. Other studies also indicated that the domains of self (low self-control) and peers (delinquent peers) were robust predictors of delinquency trajectories among South Korean adolescents (Cho & Lee, 2018, 2020aCho & Lee, 2020b). Lee et al (2018) found robust signiicance for the domain of peers and school among a nationally representative sample from the Korea Welfare Panel study (KWP) in South Korea.…”
Section: Cultural Contexts In South Koreamentioning
confidence: 98%